Knowledge, attitudes and practice of adverse drug reaction monitoring among physicians in India - Sen, Sukanta; Rahaman, Sk. Rafikul; Chatterjee, Dattatreyo; Mukherjee, Shatavisa; Mondal, Somnath; Tripathi, S. K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Underreporting of ADRs still remains a major obstacle in the complete success of pharmacovigilance programs. In order to improve ADR monitoring, it is thus imperative to assess the current knowledge, attitude, and practices of doctors. Therefore, the primary objective of this study was to evaluate the knowledge, attitude, and practices (KAP) of the healthcare professionals about pharmacovigilance in various tertiary care government teaching hospital vis-a-vis private clinics in West Bengal. Methods: A cross sectional, questionnaire based survey was conducted among healthcare practitioners in several tertiary care government set-ups and private set-ups in the state of West Bengal (India). The study instrument was a pre-validated structured questionnaire designed to obtain information on the knowledge of the ADRs reporting, the attitudes towards the reporting, and the factors that in practice could hinder the reporting among the doctors. Results: About 89.62% public practitioners correctly spotted the WHO definition for pharmacovigilance, while 77.5% of the private practitioners did the same. Only 19.81% of the public practitioners documented a suspected ADR in any surveillance form, while there were only 3.75% private practitioners who documented it. About 59.43% of the physicians in government hospitals published an ADR case report in any medical journal, while 81.25% private practitioners did no. Conclusions: Study revealed lack of time, incentive less extra work load being major factors responsible for ADR underreporting. In order to improve ADR reporting, continuous medical education, training and proper sensitization of healthcare professionals can help combating the existing scenario and promising an improved tomorrow. The PvPI should be widely publicized in the visual and print media to make health professionals, as well as the general population at large aware of its presence and scope. Pharmacovigilance should be integrated in undergraduate and postgraduate medical courses.